PROPORSI PENGGUNAAN SUMBER DAYA PROYEK PADA BANGUNAN GEDUNG DI BALI - Yuni, Ni Kadek Sri Ebtha; Sudiasa, I Wayan; Sudiarta, I Komang; Yuliana, Ni Putu Indah; Wahyudi, I Gede Bambang (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2024)
Construction projects are activities carried out with limited time and costs. In its implementation, the project requires resources, namely materials, wages, tools and decisions on the use of subcontractors. Project implementation always begins with implementation planning. This activity consists of planning work methods, calculating project resource requirements, and determining the schedule for procuring these resources. Every project implementation always has risks in it. This risk can originate from human resources, implementation methods, and work environment conditions. Due to the limited time for implementing construction projects, it is not uncommon for planning project resource requirements to experience calculation errors. This error could be a lack of budget allocated to one of the project resource components. This research was carried out with the aim of obtaining the proportion of each resource, namely materials, wages and tools, which can later be used as a reference in preparing project plans in a short time. This research was conducted on a building construction project that functions as a hotel and villa. The projects reviewed are 2 hotels, 1 villa and 1 resort. The results of this research show that the average proportion of project resource use to the total value is (1) Materials 64.45%, (2) Wages 24.75%, (3) Tools 7.64%, and (4) use of subcontractors 3 .17%. The proportion of use of material resources, equipment, wages and subcontractors is greatly influenced by the type of building construction, material specifications and work contracts.